2014
DOI: 10.1021/sb500307w
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs in Improving Biofuel Tolerance Using Combinations of Efflux Pumps

Abstract: Microbes can be engineered to produce next-generation biofuels; however, the accumulation of toxic biofuels can limit yields. Previous studies have shown that efflux pumps can increase biofuel tolerance and improve production. Here, we asked whether expressing multiple pumps in combination could further increase biofuel tolerance. Pump overexpression inhibits cell growth, suggesting a trade-off between biofuel and pump toxicity. With multiple pumps, it is unclear how the fitness landscape is impacted. To addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…The survey of RND efflux pumps in E. coli indicated the native E. coli AcrAB-TolC pump as a powerful candidate for tolerance toward several monoterpene hydrocarbons [65]. This library also contained RND efflux pumps from several other organisms that could be further optimized or used in combination with the native AcrAB system for highly enhanced tolerance phenotypes [65,74]. The AcrAB-TolC system, and specifically the AcrB protein, have been used in directed-evolution studies to further improve its activity for solvents such as 1-hexene [75], a-pinene, and 1-octanol [76] and several mutations that may affect substrate specificity or protein assembly have been identified (Figure 2).…”
Section: Reviewmentioning
confidence: 99%
“…The survey of RND efflux pumps in E. coli indicated the native E. coli AcrAB-TolC pump as a powerful candidate for tolerance toward several monoterpene hydrocarbons [65]. This library also contained RND efflux pumps from several other organisms that could be further optimized or used in combination with the native AcrAB system for highly enhanced tolerance phenotypes [65,74]. The AcrAB-TolC system, and specifically the AcrB protein, have been used in directed-evolution studies to further improve its activity for solvents such as 1-hexene [75], a-pinene, and 1-octanol [76] and several mutations that may affect substrate specificity or protein assembly have been identified (Figure 2).…”
Section: Reviewmentioning
confidence: 99%
“…This study showed that photosynthetic and cellular membranes were altered by dodecane, but the same effect was not observed with hexadecane treatment. Our research group hypothesized that cellular membrane morphology would be altered in the mutant strains when exposed to the chemicals of interest due to the damage in cellular membranes that is caused by similar chemicals [22,74,82]. However, no apparent morphological changes were observed using light microscopy (data not shown).…”
Section: Screening Mutants For Increased Tolerance To Biofuelsmentioning
confidence: 93%
“…These chemicals can damage the cell's membrane, resulting in leakage of metabolites and ions, which impacts the cells ability to maintain cellular functions [22,74, 82]. We first sought to establish the tolerance of the wildtype cyanobacterial strains used in this study to the biofuels of interest.…”
Section: Determination Of Wildtype Cyanobacterial Tolerance To Biofuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing the number of membrane transporters is notoriously difficult due to aggregation and toxicity. Overexpression of engineered small molecule transporters was explored by Turner et al in the context of two different transporters acting in tandem on different substrates [42 ]. Interestingly, pump expression indeed has an optimum between yielding highest secretion of the molecular product and lowered toxicity from transporter overexpression.…”
Section: Shortcomings and Future Workmentioning
confidence: 99%